Continuous Noninvasive Measuring of Crayfish Cardiac and Behavioral Activities - Kuklina, Iryna; Ložek, Filip; Císař, Petr; Pautsina, Aliaksandr; Buřič, Miloš; Kozák, Pavel (Journal of visualized experiments, 2019)
A crayfish is a pivotal aquatic organism that serves both as a practical biological model for behavioral and physiological studies of invertebrates and as a useful biological indicator of water quality. Even though crayfish cannot directly specify the substances that cause water quality deterioration, they can immediately (within a few seconds) warn humans of water quality deterioration via acute changes in their cardiac and behavioral activities. In this study, we present a noninvasive method that is simple enough to be implemented under various conditions due to a combination of simplicity and reliability in one model. This approach, in which the biological organisms are implemented into environmental evaluation processes, provides a reliable and timely alarm for warning of and preventing acute water deterioration in an ambient environment. Therefore, this noninvasive system based on crayfish physiological and ethological parameter recordings was investigated for the detection of changes in an aquatic environment. This system is now applied at a local brewery for controlling quality of the water used for beverage production, but it can be used at any water treatment and supply facility for continuous, real-time water quality evaluation and for regular laboratory investigations of crayfish cardiac physiology and behavior.
Keywords: reprodukovatelnost výsledků; chemické látky znečišťující vodu; kvalita vody; Environmental Monitoring; Environmental Exposure; Water Pollutants, Chemical; vystavení vlivu životního prostředí; monitorování životního prostředí; severní raci; Behavior, Animal; Animals; chování zvířat; Astacoidea; Water Quality; Reproducibility of Results; zvířata; Heart; srdce